Definição do banco de dados DOG para obtenção de ortologia em múltiplos proteomas através do padrão PVOM - Martelli, Vinicius Garibaldi (2006)
This work presents a modeling of a data base and the process created for its instantiation with the objective to store the information necessary for the application of a new form of attainment of regions of contiguous genes that had conserved its contents, order and functions between some species of organisms prokaryotes during the evolutionary process, in order to make possible the prediction of genes and unknown proteins being based on existing information already. It also presents a tool of consultations created to make possible to the user the access to this information.